2017
DOI: 10.1021/acssuschemeng.7b02756
|View full text |Cite
|
Sign up to set email alerts
|

Highly Recyclable Fluoride for Enhanced Cascade Hydrosilylation–Cyclization of Levulinates to γ-Valerolactone at Low Temperatures

Abstract: A facile and benign catalytic route has been developed to quantitatively yield γ-valerolactone (GVL; ca. 97%) from biomass-based levulinates at room temperature to 80 °C by using easily available polymethylhydrosiloxane (PMHS) and KF as the liquid H-donor and recyclable catalyst, respectively. No extra step was required to liberate GVL from the in situ-formed siloxane, and this catalytic system exhibited a lower activation energy (40.9 kJ/mol) compared to previously reported ones. The deuterium-labeled study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…This methodology is not effective for alkyl levulinates and when methyl or ethyl levulinate was reacted with Et 3 SiH in the presence of B(C 6 F 5 ) 3 as catalyst, hydrosilylation of the ketone group was observed (Scheme 2), forming siloxane ( 1 a’/1 b’ ) as the major product whereas less than 5 % GVL formation was observed. Interestingly, reaction of isolated siloxane with catalytic amounts of cesium fluoride (CsF) resulted in cyclization to form GVL which is in line with the work reported by Yang and coworkers regarding the cyclization of alkyl levulinate to GVL using fluoride as catalyst forming siloxane intermediate where fluoride acts as base to promote the subsequent cyclization [16] . However, Yang and coworkers did not isolate the siloxane intermediate 1 a’/1 b’ .…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…This methodology is not effective for alkyl levulinates and when methyl or ethyl levulinate was reacted with Et 3 SiH in the presence of B(C 6 F 5 ) 3 as catalyst, hydrosilylation of the ketone group was observed (Scheme 2), forming siloxane ( 1 a’/1 b’ ) as the major product whereas less than 5 % GVL formation was observed. Interestingly, reaction of isolated siloxane with catalytic amounts of cesium fluoride (CsF) resulted in cyclization to form GVL which is in line with the work reported by Yang and coworkers regarding the cyclization of alkyl levulinate to GVL using fluoride as catalyst forming siloxane intermediate where fluoride acts as base to promote the subsequent cyclization [16] . However, Yang and coworkers did not isolate the siloxane intermediate 1 a’/1 b’ .…”
Section: Methodssupporting
confidence: 72%
“…Although hydrosilylation is a well‐established protocol, we found that it has rarely been used for the production of GVL. Yang, Li and coworkers reported a recyclable hydrosilylation protocol with PMHS for the conversion of alkyl levulinates to GVL using KF as a catalyst [16] . In 2019, the same group reported PMHS hydrosilylation of alkyl levulinates to GVL using tetrabutylammonium fluoride TBAF as a catalyst; however, yields were modest despite high catalyst loadings and the reaction could not be applied to free LA, [17] only to esters which generally have to be synthesized from LA [18] .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, developing metal free methods for GVL synthesis has grown in interest. [21][22][23] In 2017 Yang and co-workers have reported the synthesis of GVL using KF and PMHS as a catalytic system from alkyl levulinate. [21a] KF acted here as both nucleophile as well as base for hydrosilylation and subsequent cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrosilylation of carbonyl compounds to siloxanes shows great potential in the selective synthesis of alcohols [34,35]. This type of conversion process is very attractive because the used silanes are a water-and air-stable hydrogen source, which is able to be stimulated by metal-containing catalysts under mild conditions [22,[36][37][38][39][40]. In addition, the strongly basic solvent used was proposed to facilitate its coordination with the catalytically active species (e.g., carbonate) [41], which is favorable for the reaction with silane to release hydride.…”
Section: Introductionmentioning
confidence: 99%